PERBANDINGAN METODE DESTRUKSI WET DIGESTER DENGAN MUFFLE FURNACE PADA PENENTUAN KADAR Pb2+ (TIMBAL) DALAM RAMBUT - Firdaus S. R; Saibun Sitorus (PROSIDING SEMINAR KIMIA, 2017)
An appeal has been tested for two methods of Wet Digester destruction with Muffle Furnace for determination of Pb (lead) metal ion content in hair. The Wet Digester destruction uses temperature 578oC for 4 hours and the addition of HNO3(p) at the beginning and end of destruction, while Muffle Furnace destruction uses temperature 600oC and addition of HNO3(p) at the end of destruction.Analysis of Pb (lead) metal ion content of destruction results was done with Atomic Absorption Spectrophotometer (AAS).Results of laboratory analysis that in the workers hair of heavy equipment Department Bintang PT. KPC is shown to contain Pb (lead) metal ions. To determine a more valid method of extraction performed linear regression testing, correlation coefficient, Ttabel test and determinant coefficient. The results of linear regression testing for the destruction of Wet Digester obtained r value = 0,867, the correlation coefficient r = 0,867 ≥ r table = 0,564 (positive correlation) and the coefficient of determinant % D = 75,2 %, while the results of linear regression testing for Muffle Furnace destruction obtained r value = 0,864, correlation coefficient r = 0,849 ≥ r table = 0,564 (positive correlation) and the coefficient of determinant % D = 74,8 %. The Destruksi Wet Digester is more valid than the Muffle Furnace destruction because the linear regretting value is closer to the value of r = 1 (perfect linear regression value) and the correlation coefficient and the determinant coefficient of Wet Digester destruction is higher than the correlation coefficient and the determinant coefficient of Muffle Furnace destruction . Keywords: Hair, Lead, Correlation Coefficient, Determination, Wet Digester, Muffle Furnace, Absorption Spectrophotometer (AAS)